1993
DOI: 10.1002/ddr.430290102
|View full text |Cite
|
Sign up to set email alerts
|

Problems and perspectives in the design of anti‐HIV‐1 agents

Abstract: The human immunodeficiency virus (HIV) that produces the acquired immune deficiency syndrome (AIDS) continues to evade all strategies for potential therapeutic intervention. Global efforts in the search for potential anti-HIV-I agents have mainly centered around the design of enzyme inhibitors and derivatives that inhibit viral binding or gene expression. Both nucleoside and non-nucleoside reverse transcriptase inhibitors have demonstrated potent anti-HIV-1 activity. However, toxicity considerations and the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 152 publications
0
6
0
Order By: Relevance
“…[1][2][3][4][5] The mechanism of action of AZT involves its conversion into the corresponding 5'-O-triphosphate, which inhibits the replication of the virus by competitive inhibition of the viral reverse transcriptase (RT) and by incorporation and subsequent chain termination of the growing viral DNA strand. [6] Despite the development of additional RT inhibitors and agents that block other crucial steps in viral infection and replication, AZT is still the most used anti-HIV agent. However, administration of AZT is frequently associated with a significant dose-dependent toxicity, particularly destruction of bone marrow cells, myopathy, and hepatic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The mechanism of action of AZT involves its conversion into the corresponding 5'-O-triphosphate, which inhibits the replication of the virus by competitive inhibition of the viral reverse transcriptase (RT) and by incorporation and subsequent chain termination of the growing viral DNA strand. [6] Despite the development of additional RT inhibitors and agents that block other crucial steps in viral infection and replication, AZT is still the most used anti-HIV agent. However, administration of AZT is frequently associated with a significant dose-dependent toxicity, particularly destruction of bone marrow cells, myopathy, and hepatic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…In the DNA polymerase assay, the most active naphthalensulfonic acid compounds fall into two broad structural classes. Compounds 2, 4, and [16][17][18] the symmetrical class of derivatives consisting of either a flexible polymethylene spacer or an aromatic spacer, while compounds 1, 6, 23, 24, 26, and 27 are nonsymmetrical derivatives having lipophilic palmitoyl or cholesteryl moieties. We have previously reported that compound 1 possesses potent inhibitory activities towards recombinant HIV-1 and HIV-2 RT, which was superior to the known RT inhibitor, Suramin.7 On the basis of the above data, derivatives 6,16, 17, 23, 26, and 27 were chosen for determinations of 50% inhibitory concentration (IC50) values for the inhibition of RNA-dependent DNA polymerase activity (RDDP), DNA-dependent DNA polymerase activity (DDDP), and ribonuclease H (RNase H) activity of RT (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Zidovudine (AZT, 3′-azido-3′-deoxythymidide, 19 , Figure 9 ) was the first 2′-3′-dideoxy-nucleoside (ddN) approved by US Food and Drug Administration (FDA) for treatment of patients suffering from AIDS [ 53 , 54 ]. The mechanism of action of 19 involves its conversion into the corresponding 5′- O -triphosphate, which inhibits the replication of the virus by competitive inhibition of the viral reverse transcriptase (RT) and by incorporation and subsequent chain termination of the growing viral strand [ 55 ]. Administration of 19 is frequently associated with a significant dose-dependent toxicity, additionally to its short half-time in human plasma which requires frequent administration to maintain therapeutic drug concentrations [ 56 , 57 ].…”
Section: Drugs and Diseasesmentioning
confidence: 99%